Distribution of sulfate-reducing bacteria in a stratified fjord (Mariager Fjord, Denmark) as evaluated by most-probable-number counts and denaturing gradient gel electrophoresis of PCR-amplified ribosomal DNA fragments. - Teske, A (1996)
The sulfate-reducing bacterial populations of a stratified marine water column, Mariager Fjord, Denmark, were investigated by molecular and culture-dependent approaches in parallel. Denaturing gradient gel electrophoresis (DGGE) of PCR-amplified 16S rRNA and DNA encoding rRNA (rDNA) isolated from the water column indicated specific bacterial populations in different water column layers and revealed a highly differentiated pattern of rRNA- and rDNA-derived PCR amplificates, probably reflecting active and resting bacterial populations. Hybridization of DGGE patterns with rRNA probes indicated the increased presence and activity (by at least 1 order of magnitude) of sulfate-reducing bacteria within and below the chemocline. Parallel to this molecular approach, an approach involving most-probable-number (MPN) counts was used, and it found a similar distribution of cultivable sulfate-reducing bacteria in the water column of Mariager Fjord, Approximately 25 cells and 250 cells per ml above and below the chemocline, respectively, were found. Desulfovibrio- and Desulfobulbus-related strains occurred in the oxic zone. DGGE bands from MPN cultures were sequenced and compared with those obtained from nucleic acids extracted from water column samples. The MPN isolates were phylogenetically affiliated with sulfate-reducing delta subdivision proteobacteria (members of the genera Desulfovibrio, Desulfobulbus, and Desulfobacter), whereas the molecular isolates constituted an independent lineage of the delta subdivision proteobacteria. DGGE of PCR-amplified nucleic acids with general eubacterial PCR primers conceptually revealed the general bacterial population, whereas the use of culture media allowed cultivable sulfate-reducing bacteria to be selected. A parallel study of Mariager Fjord biogeochemistry, bacterial activity, and bacterial counts complementing this investigation has been presented elsewhere (N.B. Ramsing, H. Fossing, T. G. Ferdelman, F. Andersen, and B. Thamdrup, Appl. Environ.